High-temperature-resistant wave-transparent hole sealing coating and preparation method thereof

By using polyamic acid/nano silica composite coating, the problems of high water absorption and wave-transmissive performance deterioration caused by the microporous structure of the surface of high-temperature wave-transmissive composite materials are solved, and the high-performance pore sealing, high-temperature resistance and Improved hydrophobic performance.

CN119432226APending Publication Date: 2025-02-14AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411714725.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

There is a microporous structure on the surface of existing high-temperature wave-resistant composite materials, resulting in high water absorption, increased dielectric constant and dielectric loss, deteriorating wave-transmissive performance, and insufficient temperature resistance, hydrophobic performance and adhesion of the coating.

Method used

Polyamic acid/nanosilica composite coating is used to prepare fluoropolymeric polyamic acid by solution polymerization, and nanosilica is used as a sealing filler, combining two-component organic solvents and functional additives to form a high-performance sealing Pore ​​paint.

Benefits of technology

The coating has excellent spraying process performance and pore sealing characteristics, which can effectively solve the porous defects on the surface of the composite material, improve the surface density, and show excellent high temperature resistance, wave transmissiveness, hydrophobic properties and adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432226A_ABST
    Figure CN119432226A_ABST
Patent Text Reader

Abstract

The invention relates to a high-temperature-resistant wave-transparent hole sealing coating and a preparation method thereof. The coating is compounded by taking fluorine-containing polyamide acid as a carrier, nano silicon dioxide as a hole sealing filler and a two-component organic solvent as a diluent and adding functional aids such as a dispersing agent, a defoaming agent and a flatting agent. The preparation method of the coating comprises the following steps: firstly, preparing a nano silicon dioxide dispersion liquid, and then sequentially adding fluorine-containing aromatic diamine and 3, 3 '-diaminodiphenylmethane into the dispersion liquid; the high-temperature-resistant wave-transparent hole-sealing coating is prepared by adding fluorine-containing polyamide acid into nano silicon dioxide, adding 3, 3 ', 4, 4'-benzophenonetetracarboxylic dianhydride, stirring and reacting to obtain a high-viscosity nano silicon dioxide / fluorine-containing polyamide acid mixed glue solution, finally adding an organic solvent and a functional additive, and mixing and stirring uniformly to obtain the high-temperature-resistant wave-transparent hole-sealing coating. A coating layer formed by high-temperature curing of the coating has excellent temperature resistance, hole sealing property and hydrophobic property, can overcome the surface porous defect of a high-temperature-resistant resin-based wave-transparent composite material and reduce the water absorption rate of the high-temperature-resistant resin-based wave-transparent composite material, and in addition, the coating layer also has excellent wave-transparent property and adhesive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave-transmitting composite materials, and in particular relates to a high-temperature resistant wave-transmitting sealing coating and a preparation method thereof. Background Art

[0002] Fiber-reinforced resin-based wave-transparent composite materials are the core materials of radar covers. While ensuring radar communication, they can significantly improve the protection performance of radar systems. As the flight speed of aircraft continues to rise, more stringent requirements are placed on the temperature resistance of radar covers. The application of high-temperature resistant resin-based wave-transparent composite materials represented by polyimide and polyarylene has increased rapidly. However, due to the limitations of material types and molding processes, high-temperature resistant composite materials usually have a large number of microporous structures on their surfaces after molding. These microporous structures provide channels for the penetration of water molecules, thereby significantly increasing the water absorption rate of the composite material, which in turn causes the dielectric constant and dielectric loss of the composite material to increase, and deteriorates the wave-transparent performance of the composite material.

[0003] Constructing coatings is a common method to improve the surface quality of composite materials. Spraying sealing coatings can fill the microporous defects on the surface of composite materials. However, according to public reports, the current sealing coatings are usually made of epoxy resins and polyurethane resins as film-forming materials, and inorganic particles such as mica powder and talcum powder as fillers. There are three problems with this type of sealing coating. First, the temperature resistance of the coating is insufficient and can usually only meet the use requirements below 300°C; second, the dielectric constant and dielectric loss of the coating are generally large, and using it to modify composite materials will usually reduce the wave transmission performance of the composite materials; third, the hydrophobicity of the coating itself is poor.

[0004] In summary, there is currently a lack of surface sealing coatings suitable for high-temperature resistant resin-based wave-transmitting composite materials such as polyimide, polyarylene, and phthalonitrile. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a polyamic acid / nano-silicon dioxide composite coating suitable for surface sealing of high-temperature resistant fiber-reinforced resin-based wave-transmitting composite materials and a preparation method thereof.

[0006] In a first aspect, the present invention relates to a high temperature resistant wave-transmitting sealing coating, which is compounded with fluorine-containing polyamic acid as a carrier, nano-silicon dioxide as a sealing filler, a two-component organic solvent as a diluent, and a functional additive.

[0007] The polyamic acid is prepared by solution polymerization of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride and fluorinated aromatic diamine, wherein 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride can enhance the adhesion of the coating, and the fluorinated aromatic diamine gives the coating excellent solubility and hydrophobicity. The fluorinated aromatic diamine includes: any one of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(4-aminophenyl)hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, or a mixture of any of them in any proportion.

[0008] Among them, the nano-silica is hydrophobic nano-silica with a particle size of 20 to 100 nm, which provides hydrophobic properties for the coating.

[0009] The diluent is composed of two types of solvents, organic solvent A and organic solvent B. Organic solvent A is a high-polarity amide solvent, specifically any one of N,N-dimethylformamide, N,N-dimethylformamide, and N-methylpyrrolidone, or a mixture of any of them in any proportion, and the solvent has good solubility for polyamic acid; organic solvent B is a low surface tension, low boiling point organic solvent, specifically any one of ethyl acetate, butyl acetate, butanone, acetone, and tetrahydrofuran, or a mixture of any of them in any proportion, and the solvent is used to improve the spraying process performance of the coating.

[0010] Functional additives include dispersants, defoamers, leveling agents, etc.

[0011] In a second aspect, the present invention discloses a method for preparing a high temperature resistant wave-transmitting sealing coating, the method for preparing the sealing coating specifically comprising the following steps:

[0012] 1) Add nano-silicon dioxide and a dispersant into an organic solvent A, and perform ultrasonic stirring and dispersion to obtain a nano-silicon dioxide dispersion.

[0013] 2) Dissolving a certain amount of fluorine-containing aromatic diamine in the nano-silicon dioxide dispersion.

[0014] 3) After the fluorinated aromatic diamine is completely dissolved, a certain amount of 3,3',4,4'-benzophenonetetracarboxylic dianhydride is added to the above dispersion, and the mixture is stirred and reacted at room temperature for more than 12 hours to obtain a high-viscosity nano-silica / fluorinated polyamic acid mixed adhesive.

[0015] 4) Adding organic solvent B and functional additives to the above glue solution, stirring at high speed to obtain a high temperature resistant and wave-transmitting sealing coating.

[0016] The nano-silica in step 1) is hydrophobic nano-silica with a particle size of 20-100 nm.

[0017] The solid content of nano-silicon dioxide in the nano-silicon dioxide dispersion in step 1) is 10-20%.

[0018] In the step 2), the fluorinated aromatic diamine is any one of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(4-aminophenyl)hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, or a mixture of any of them in any proportion.

[0019] In the step 2), the solid content of the fluorinated aromatic diamine in the organic solvent A is 15-20%.

[0020] In the step 3), the molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to fluorine-containing aromatic diamine is 1:(0.9-1.1).

[0021] In the step 4), the organic solvent B is any one of ethyl acetate, butyl acetate, butanone, acetone, and tetrahydrofuran, or a mixture of any of them in any proportion.

[0022] In the step 4), the mass of the organic solvent B is 3 to 4 times the mass of the solvent A.

[0023] The functional additives in step 4) include defoamers and leveling agents. The amount of the defoamer is 0.5-1% of the total mass of the sealing coating, and the amount of the leveling agent is 1%-2% of the total mass of the sealing coating.

[0024] The beneficial effects of the present invention are as follows: the present invention provides a polyamic acid / nano-silicon dioxide composite coating suitable for surface sealing of high-temperature resistant fiber-reinforced resin-based wave-transmitting composite materials and a preparation method thereof, the coating has excellent spraying process performance and sealing characteristics, can solve the surface porous defects of high-temperature resistant resin-based wave-transmitting composite materials, and improve the surface density of the composite materials. In addition, the coating also has excellent high-temperature resistance, wave-transmitting performance, hydrophobicity and adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a microscopic photograph of the surface of the composite material before coating construction in Example 1.

[0026] Figure 2 This is a microscopic photograph of the surface of the composite material after the coating is constructed in Example 1.

[0027] Figure 3 This is a microscopic photograph of the surface of the composite material after the coating is constructed in Example 2.

[0028] Figure 4 This is a microscopic photograph of the surface of the composite material after the coating was constructed in Example 3.

[0029] Figure 5 This is a microscopic photograph of the surface of the composite material after the coating was constructed in Example 4. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below through specific embodiments and drawings.

[0031] Embodiment 1:

[0032] 10.00 g of hydrophobic nano-silica (particle size 20 nm) was weighed and added to 56.67 g of N,N-dimethylacetamide, and stirred with ultrasound for 30 minutes to obtain a nano-silica dispersion.

[0033] Furthermore, 22.50 g (0.07026 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminohydrazine was weighed and added into the nano-silicon dioxide dispersion, and stirred to dissolve.

[0034] Furthermore, 20.38 g (0.06323 mol) of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride was weighed and added to the above dispersion, and the mixture was stirred and reacted at room temperature for more than 12 hours to allow the fluorinated aromatic diamine and 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride to fully polymerize and obtain a high-viscosity nano-silica / fluorinated polyamic acid mixed adhesive.

[0035] Furthermore, 270 g of ethyl acetate, 2.09 g of tributyl phosphate (defoaming agent) and 4.19 g of silicone leveling agent were added to the mixed glue solution, and stirred at high speed to obtain the high temperature resistant and wave-transmitting resin-based composite material sealing coating.

[0036] The coating was sprayed on a clean glass slide, and after curing at 40℃ / 1 hour, 120℃ / 1 hour, 200℃ / 1 hour, and 300℃ / 1 hour, a high temperature resistant coating was obtained. After peeling off the glass slide, the heat resistance and dielectric properties of the coating were tested respectively. Table 1 lists the dielectric constant and dielectric loss of the coating at 5% weight loss temperature in air and 10GHz.

[0037] The coating was further sprayed on a quartz fiber reinforced polyarylene composite material plate for surface modification. The coating was sprayed 5 times with an interval of 15 seconds between each time. The plate was then placed in an electric hot air drying oven for curing. After curing at 40°C / 1 hour, 120°C / 1 hour, 200°C / 1 hour, and 300°C / 1 hour, the surface coating of the composite material was completed. Figure 1 and Figure 2The microscopic photos of the composite surface before and after the coating are respectively shown. It can be seen that the micropores on the surface of the composite are completely covered by the coating. Table 1 lists the water contact angle value and adhesion grade (cross-cut test method) of the coating surface. From the morphology photos and test data, it can be seen that the coating has excellent heat resistance, low dielectric constant and loss, pore sealing, hydrophobicity and adhesion.

[0038] Embodiment 2:

[0039] 10.00 g of hydrophobic nano-silica (particle size 50 nm) was weighed and added into 90 g of N,N-dimethylformamide, and stirred for 30 minutes with ultrasonic assistance to obtain a nano-silica dispersion.

[0040] Furthermore, 11.61 g (0.03472 mol) of 2,2'-bis(4-aminophenyl)hexafluoropropane was weighed and added into the nano-silicon dioxide dispersion, and stirred to dissolve.

[0041] Furthermore, 11.19 g (0.03472 mol) of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride was weighed and added to the above dispersion, and the mixture was stirred and reacted at room temperature for more than 12 hours to allow the fluorinated aromatic diamine and 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride to fully polymerize and obtain a high-viscosity nano-silica / fluorinated polyamic acid mixed adhesive.

[0042] Furthermore, 238.97 g of acetone, 2.52 g of tributyl phosphate (defoaming agent), and 5.04 g of an organosilicon leveling agent were added to the mixed glue solution, and stirred at high speed to obtain the high-temperature resistant and wave-transmitting resin-based composite material sealing coating.

[0043] The coating was sprayed on a clean glass slide, and after curing at 40℃ / 1 hour, 120℃ / 1 hour, 200℃ / 1 hour, and 300℃ / 1 hour, a high temperature resistant coating was obtained. After peeling off the glass slide, the heat resistance and dielectric properties of the coating were tested respectively. Table 1 lists the dielectric constant and dielectric loss of the coating at 5% weight loss temperature in air and 10GHz.

[0044] The coating was further sprayed on a quartz fiber reinforced polyarylene composite material plate for surface modification. The coating was sprayed 5 times with an interval of 15 seconds between each time. The plate was then placed in an electric hot air drying oven for curing. After curing at 40°C / 1 hour, 120°C / 1 hour, 200°C / 1 hour, and 300°C / 1 hour, the surface coating of the composite material was completed. Figure 3 The microscopic photo of the composite surface after coating construction shows that the micropores on the composite surface are completely covered by the coating. Table 1 lists the water contact angle value and adhesion grade (cross-cut test method) of the coating surface. From the morphology photos and test data, it can be seen that the coating has excellent heat resistance, low dielectric constant and loss, pore sealing, hydrophobicity and adhesion.

[0045] Embodiment 3:

[0046] 10.00 g of hydrophobic nano-silicon dioxide (particle size 100 nm) was weighed and added to 40 g of N-methylpyrrolidone, and ultrasonic-assisted stirring was performed for 30 minutes to obtain a nano-silicon dioxide dispersion.

[0047] Furthermore, 7.06 g (0.01362 mol) of 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane was weighed and added into the nano-silicon dioxide dispersion, and stirred to dissolve.

[0048] Furthermore, 4.83 g (0.01498 mol) of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride was weighed and added to the above dispersion, and the mixture was stirred and reacted at room temperature for more than 12 hours to allow the fluorinated aromatic diamine and 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride to fully polymerize and obtain a high-viscosity nano-silica / fluorinated polyamic acid mixed glue.

[0049] Furthermore, 160.00 g of butyl acetate, 2.29 g of an organosilicon defoaming agent, and 4.57 g of an organosilicon leveling agent were added to the mixed glue solution, and stirred at high speed to obtain the high-temperature resistant and wave-transmitting resin-based composite material sealing coating.

[0050] The coating was sprayed on a clean glass slide, and after curing at 40℃ / 1 hour, 120℃ / 1 hour, 200℃ / 1 hour, and 300℃ / 1 hour, a high temperature resistant coating was obtained. After peeling off the glass slide, the heat resistance and dielectric properties of the coating were tested respectively. Table 1 lists the dielectric constant and dielectric loss of the coating at 5% weight loss temperature in air and 10GHz.

[0051] The coating was further sprayed on a quartz fiber reinforced polyarylene composite material plate for surface modification. The coating was sprayed 5 times with an interval of 15 seconds between each time. The plate was then placed in an electric hot air drying oven for curing. After curing at 40°C / 1 hour, 120°C / 1 hour, 200°C / 1 hour, and 300°C / 1 hour, the surface coating of the composite material was completed. Figure 4 The microscopic photo of the composite surface after coating construction shows that the micropores on the composite surface are completely covered by the coating. Table 1 lists the water contact angle value and adhesion grade (cross-cut test method) of the coating surface. From the morphology photos and test data, it can be seen that the coating has excellent heat resistance, low dielectric constant and loss, pore sealing, hydrophobicity and adhesion.

[0052] Embodiment 4:

[0053] 10.00 g of hydrophobic nano-silicon dioxide (particle size 20 nm) was weighed and added into 90 g of N-methylpyrrolidone, and stirred for 30 minutes with ultrasonic assistance to obtain a nano-silicon dioxide dispersion.

[0054] Furthermore, 10.00 g (0.03123 mol) of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 12.50 g (0.03796 mol) of 2,2'-bis(4-aminophenyl)hexafluoropropane were weighed and added into the nano-silica dispersion, and stirred to dissolve.

[0055] Furthermore, 22.11 g (0.06862 mol) of 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride was weighed and added to the above dispersion, and the mixture was stirred and reacted at room temperature for more than 12 hours to allow the fluorinated aromatic diamine and 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride to fully polymerize and obtain a high-viscosity nano-silica / fluorinated polyamic acid mixed glue.

[0056] Furthermore, 270 g of tetrahydrofuran, 2.10 g of a defoaming agent, and 4.21 g of a leveling agent were added to the mixed adhesive solution, and stirred at a high speed to obtain the high-temperature resistant and wave-transmitting resin-based composite material sealing coating.

[0057] The coating was sprayed on a clean glass slide, and after curing at 40℃ / 1 hour, 120℃ / 1 hour, 200℃ / 1 hour, and 300℃ / 1 hour, a high temperature resistant coating was obtained. After peeling off the glass slide, the heat resistance and dielectric properties of the coating were tested respectively. Table 1 lists the dielectric constant and dielectric loss of the coating at 5% weight loss temperature in air and 10GHz.

[0058] The coating was further sprayed on a quartz fiber reinforced polyarylene composite material plate for surface modification. The coating was sprayed 5 times with an interval of 15 seconds between each time. The plate was then placed in an electric hot air drying oven for curing. After curing at 40°C / 1 hour, 120°C / 1 hour, 200°C / 1 hour, and 300°C / 1 hour, the surface coating of the composite material was completed. Figure 5 The microscopic photo of the composite surface after coating construction shows that the micropores on the composite surface are completely covered by the coating. Table 1 lists the water contact angle value and adhesion grade (cross-cut test method) of the coating surface. From the morphology photos and test data, it can be seen that the coating has excellent heat resistance, low dielectric constant and loss, pore sealing, hydrophobicity and adhesion.

[0059] Table 1

[0060]

[0061] The specific embodiments of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various replacements, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.

Claims

1. A high temperature resistant wave-transmitting sealing coating, characterized in that: The sealing coating is prepared by using fluorine-containing polyamic acid as a carrier, nano silicon dioxide as a sealing filler, a two-component organic solvent as a diluent, and adding a functional auxiliary agent.

2. The high temperature resistant wave-transmitting sealing coating according to claim 1, characterized in that: The fluorine-containing polyamic acid is prepared by solution polymerization using 3,3',4,4'-benzophenonetetracarboxylic dianhydride and fluorine-containing aromatic diamine; the fluorine-containing aromatic diamine includes: any one of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(4-aminophenyl)hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, or a mixture of at least two of them in any proportion.

3. The high temperature resistant wave-transmitting sealing coating according to claim 1, characterized in that: The nano silicon dioxide is hydrophobic nano silicon dioxide with a particle size of 20 to 100 nm.

4. The high temperature resistant wave-transmitting sealing coating according to claim 1, characterized in that: The diluent is composed of two types of solvents, an organic solvent A and an organic solvent B; the organic solvent A is a high-polarity amide solvent, and the organic solvent B is a low-surface tension, low-boiling point organic solvent; the organic solvent A is any one of N,N-dimethylformamide, N,N-dimethylformamide, and N-methylpyrrolidone, or a mixture of at least two of them in any proportion; the organic solvent B is any one of ethyl acetate, butyl acetate, butanone, acetone, and tetrahydrofuran, or a mixture of at least two of them in any proportion.

5. The high temperature resistant wave-transmitting sealing coating according to claim 1, characterized in that: The functional additives include dispersants, defoamers and leveling agents.

6. A method for preparing a high temperature resistant wave-transmitting sealing coating, characterized in that: The following steps are involved: 1) adding nano-silicon dioxide and a dispersant into an organic solvent A, and performing ultrasonic stirring and dispersion to obtain a nano-silicon dioxide dispersion; 2) dissolving the fluorine-containing aromatic diamine in the nano-silicon dioxide dispersion; 3) adding 3,3',4,4'-benzophenonetetracarboxylic dianhydride to the dispersion in which the fluorinated aromatic diamine is dissolved, and stirring the mixture at room temperature for more than 12 hours to obtain a high-viscosity nano-silica / fluorinated polyamic acid mixed adhesive; 4) Adding organic solvent B and functional additives to the mixed glue solution, stirring at high speed, and obtaining a high temperature resistant and wave-transmitting sealing coating.

7. The preparation method according to claim 6, characterized in that: The nano silicon dioxide in step 1) is hydrophobic nano silicon dioxide with a particle size of 20-100 nm; the solid content of nano silicon dioxide in the nano silicon dioxide dispersion is 10-20%.

8. The preparation method according to claim 6, characterized in that: In the step 2), the fluorine-containing aromatic diamine is any one of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(4-aminophenyl)hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, or a mixture of at least two of them in any proportion; the solid content of the fluorine-containing aromatic diamine in the organic solvent A is 15-20%.

9. The preparation method according to claim 6, characterized in that: In the step 3), the molar ratio of 3,3',4,4'-benzophenonetetracarboxylic dianhydride to fluorine-containing aromatic diamine is 1:(0.9-1.1).

10. The preparation method according to claim 6, characterized in that: In the step 4), the organic solvent B is any one of ethyl acetate, butyl acetate, butanone, acetone, and tetrahydrofuran, or a mixture of at least two of them in any proportion; the mass of the organic solvent B is 3 to 4 times the mass of the organic solvent A; the functional additives in the step 4) include a defoamer and a leveling agent, the amount of the defoamer is 0.5 to 1% of the total mass of the sealing coating, and the amount of the leveling agent is 1% to 2% of the total mass of the sealing coating.

Citation Information

Patent Citations

  • Hydrophobic coating composition and preparation method thereof, and product

    CN112063208A

  • High-temperature-resistant wave-transparent polyimide coating as well as preparation method and application thereof

    CN117050652A